Current Status of Probiotics as Supplements in the Prevention and Treatment of Infectious Diseases - Li, Xinquan; Wang, Qiang; Hu, Xiafen; Liu, Wanxin (Frontiers in Cellular and Infection Microbiology, 2022)
Probiotics play an important role against infectious pathogens via their effects on epithelium, production of antimicrobial compounds and competitive exclusion. Administration of probiotic supplements may reduce the risk of infectious diseases and the use of antibiotics and hence contribute to a reduction or a delay of the development of multi resistant bacteria. For people who are experiencing recurrent infections, infection is a constant concern and usually failed in antibiotic treatment due to the antibiotic resistance, the infection can lead to severe illness and hospitalization if left untreated. A growing number of studies have demonstrated promising results for a variety of probiotic strains to prevent or treat acute and recurrent infectious diseases, but additional standardized clinical research is needed.